Validity of Self-reported Cannabis Use Among Pregnant Females in Northern California. Issue 4 (July 2020) - Young-Wolff, Kelly C.; Sarovar, Varada; Tucker, Lue-Yen; Goler, Nancy; Conway, Amy; Weisner, Constance; Armstrong, Mary Anne; Alexeeff, Stacey
Abstract : Background: Most clinical and epidemiologic estimates of prenatal cannabis use are based on self-report, and the validity of self-reported cannabis use has not been examined in a large, representative population of pregnant women. We determined the validity of self-reported prenatal cannabis use and predictors of nondisclosure using data from Kaiser Permanente Northern California's (KPNC) healthcare system with universal prenatal cannabis screening during prenatal care. Methods: Validation study using data from 281, 025 pregnancies in KPNC among females aged ≥11 years who completed a self-administered questionnaire on prenatal cannabis use and a cannabis urine toxicology test from 2009 to 2017. We calculated sensitivity, specificity, positive predictive value, and negative predictive value of self-reported prenatal cannabis use using urine toxicology testing as the criterion standard, and sensitivity of urine toxicology testing using self-reported use as the criterion standard. We compared sociodemographics of those who disclosed versus did not disclose prenatal cannabis use. Results: Urine toxicology testing identified more instances of prenatal cannabis use than self-report (4.9% vs 2.5%). Sensitivity of self-reported use was low (33.9%). Sensitivity of the toxicology test was higher (65.8%), with greater detection of self-reported daily (83.9%) and weekly (77.4%) than monthly or less use (54.1%). Older women, those of Hispanic race/ethnicity, and those with lower median neighborhood incomes were most likely to be misclassified as not using cannabis by self-reported screening. Conclusions: Given that many women choose not to disclose prenatal cannabis use, clinicians should educate all prenatal patients about the potential risks and advise them to quit cannabis use during pregnancy. Abstract : Supplemental Digital Content is available in the text